Towards the development of asymmetric 6Pi electrocyclisations - Parra, Guillaume (2014)
The biosynthesis of the superfamily of pyrones such as (+)-tridachione, (-)-crispatone or tridachiahydropyrone have drawn much attention. However, the isolated natural products are enantiomerically pure whereas the syntheses of these natural products were completed in racemic form. This raises the question of where, in nature, the chirality is derived from. It has been hypothesized that the all (E)-polyene tridachiahydropyrone precursor is present in the membrane of the producing mollusc, and during the reaction the membrane provides a favourable chiral environment for obtaining only the tridachiahydropyrone enantiomer. The project aims to use different systems that mimic the cell membrane of the sacoglossan to show that a chiral environment induce chirality for electrocyclisations such as beta-cyclodextrin and chiral liquid crystals. Also, our efforts were towards the development of novel asymmetric 6Pi electrocyclic reactions that exploit catalyst-induced enantioselectivity with a secondary amine such as proline or (S)-alpha,alpha-diphenylprolinol, (S)-alpha,alpha-diphenylprolinol silylether, and MacMillan’s catalyst second generation. Unfortunately, all these electrocyclic reactions gave a racemic mixture